The parasporal crystals of Bacillus pumilus strain 15.1: a potential virulence factor? - Garcia‐Ramon, Diana C. (Microb Biotechnol, 2017)
Bacillus pumilus strain 15.1 was previously found to cause larval mortality in the Med‐fly Ceratitis capitata and was shown to produce crystals in association with the spore. As parasporal crystals are well‐known as invertebrate‐active toxins in entomopathogenic bacteria such as Bacillus thuringiensis (Cry and Cyt toxins) and Lysinibacillus sphaericus (Bin and Cry toxins), the B. pumilus crystals were characterized. The crystals were composed of a 45 kDa protein that was identified as an oxalate decarboxylase by peptide mass fingerprinting, N‐terminal sequencing and by comparison with the genome sequence of strain 15.1. Synthesis of crystals by a plasmid‐cured derivative of strain 15.1 (produced using a novel curing strategy), demonstrated that the oxalate decarboxylase was encoded chromosomally. Crystals spontaneously solubilized when kept at low temperatures, and the protein produced was resistant to trypsin treatment. The insoluble crystals produced by B. pumilus 15.1 did not show significant toxicity when bioassayed against C. capitata larvae, but once the OxdD protein was solubilized, an increase of toxicity was observed. We also demonstrate that the OxdD present in the crystals has oxalate decarboxylate activity as the formation of formate was detected, which suggests a possible mechanism for B. pumilus 15.1 activity. To our knowledge, the characterization of the B. pumilus crystals as oxalate decarboxylase is the first report of the natural production of parasporal inclusions of an enzyme.